Ang Kalbaryo - Arao, Hans Pieter L. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
Ang Kalbaryo (The Suffering) is set in the town of Enrile, Cagayan, during the tail-end of the Philippine Revolution in 1900, as Emilio Aguinaldo and his remnant forces flee from town to town to evade capture by the American forces. The one-act play attempts to explore the theme of war, particularly the possible roles that hunger and weariness play in planting the seeds of doubt that make a soldier question the reasons for armed struggle and eventually in committing acts of betrayal.